Feedforward control of double-panel casing for active reduction of device noise - Stanislaw Wrona; Marek Pawelczyk (Journal of Low Frequency Noise, Vibration and Active Control, 2019)
The active casing approach is a technique to reduce noise emission of devices and machinery by controlling vibrations of their casings. This method was successfully validated by the authors for a single-panel casing in previous publications. However, if even higher noise reduction is required, a dedicated double-panel structure can be employed. In this paper, the sound insulation efficiency of a double-panel active casing is evaluated and compared with a single-panel structure by performing a series of laboratory experiments. The least mean squares algorithm is used to adaptively update control filter parameters. A low-frequency noise in the range up to 500 Hz is considered. Advantages and limits of the proposed approach are pointed out and discussed, and conclusions for future research are given.